Alkali cation- interactions in aqueous systems, modulating supramolecular stereoisomerism of nanoscopic metal-organic capsules - Schmitt, Wolfgang; Watson, Graeme (My University, 2024)
Contrary to common chemical intuition, cation-π interactions can persist in polar, aqueous reaction solutions, rather than in dry non-coordinative solvent systems. This account highlights how alkali ion-π interactions impart distinctive structure-influencing supramolecular forces that can be exploited in the preparation of nanoscopic metal-organic capsules. The incorporation of alkali ions from polar solutions into molecular pockets promotes the assembly of otherwise inaccessible capsular entities whose structures are distinctive to those of common polyoxovanadate clusters in which {V=O} moieties usually point radially to the outside, shielding the molecular entities. The applied concept is exemplified by homologous {V20} and {V30} cages, composed of inverted, hemispherical {V5O9} units. The number and geometrical organization of these {V5O9} sub-units in these cages are associated with prevailing cation-π interactions and competing steric effects. The stereoisomers of these resulting nano-sized objects are comparable to Alfred Werner-type structural isomers of simple mononuclear complexes in-line with fundamental coordination chemistry principles.
PUBLISHED
Keywords: Nanoscience & Materials; Smart & Sustainable Planet; COMPLEXES; Crystal engineering; Inorganic Chemistry; MOLECULAR-STRUCTURE; Nanochemistry; Nanotechnology; New materials, supramolecular structures; Solid state chemistry; Spectroscopy; Synthesis and new molecules